Primary Aortoenteric Fistula after Nissen Fundoplication - Bixby, Catherine (Cureus, 2018)
We present the rare case of a primary gastro-aortic fistula involving the native aorta and proximal stomach in a patient with a chronic gastric ulcer and prior history of Nissen fundoplication. Our case highlights the importance of keeping this rare and fatal condition as a differential diagnosis in patients with prior history of Nissen fundoplication surgery.